(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
Sandwich Structure with pin core is widely used in foam core for crushing, debonding and interfacial delamination prevention; this structure has manufactured by drilling foam core frequently. On the other hand, a novel method for manufacturing a pin core sandwich structure has been the aim of this research. Machinable wax panel was used to achieve cavities in form of pin within the core by drilling the wax panel by CNC-drilling machine then casting of thermoset resin (unsaturated polyester resin) into a wax mold, after that melting of the wax mold to get pin core sandwich structure. Complex structure can't be designed by conventional method but by this method allows to design such complex structures: spheres, pyramids, ellipse…etc. According to Response Surface Methodology method, fifteen specimens were achieved and three variables were investigated to get optimization and prediction model. The results show that 300% improvement of stiffness performance index with 40% weight reduction comparative to reference sample with 4.46 GPa0.5 cm3 g-1 optimal value for the specimen ((High=11mm), (Diameter=9 mm) and (Pin-to-Pin distance=4.3 mm)). Strength performance index improvement is 126% and 50% weight reduction comparative to reference sample with 35.9 MPa2/3 cm3 g-1 optimal value for the specimen ((High=11mm), (Diameter=6.115 mm) and Pin-to-Pin distance=1.5 mm)). ANOVA analysis shows that the pin height (H) is effective parameter on stiffness property. On the other hand, the height and diameter of the pin are effective parameters on strength property.